Definition and Implementation of Regional Autonomy in Indonesia - Anak agung Istri Satya Nareswari Putri Markandeya (Focus Journal : Law Review, 2025)
One of the government's important policies in the renewal order is the implementation of regional autonomy which is useful for increasing the prestige of the region in the form of subsidies and plays an important role in managing regional financial and revenue potential. Basically, empowering with a larger share is directed at the goal of exploring all the existing potential, both natural and natural resources of the community, to improve the regional economy with insight into growth and income distribution. The principle of implementing regional autonomy in Indonesia is broadly organized, factual and accountable. Expanded autonomy is the regional decision-making power to complete governance including the government in all areas of government except for powers in foreign policy, defense and security, justice, monetary and finance, religion and other areas of authority regulated by government regulations. In addition, autonomy includes full authority to unite in operations from execution to execution with evaluation. The real meaning of autonomy is regional decision-making, implementation of government authority in certain areas that actually exist, needs, growth and development in the region. Meanwhile, the meaning of responsible autonomy is in the form of realizing responsibility as a consequence suffered by the regions to achieve the goals of autonomy, in the form of improving services and better social protection, developing a democratic, just and equal life and maintaining harmonious relations between the center and regions, as well as between regions. to maintain the unity of the Unitary State of the Republic of Indonesia. Regional autonomy policy, starting with the promulgation of Law no. 22 of 1999 became Law no. 23 of 2014 is the government's highest effort to find the local government formula that best suits the expectations of the whole community, but in the implementation process, many factors influence it. And to achieve optimal results still requires time and effort. But we have to be optimistic that at least the process of changing management of modernizing local government has started. Keywords: Principles, Concepts, Regional Autonomy